The Impact of Agricultural Market Liberalisation from a Gender Perspective: Evidence from Uganda - Jann Lay; Jennifer Golan (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Focusing on intra-household allocation, we investigate the effects of coffee market liberalisation in Uganda. As coffee has traditionally been a male domain, higher income from this activity might increase gender disparities. In addition, gender-related inefficiency in household production might undermine the positive impact of improved incentives. Using data from three household surveys conducted between 1992 and 2006, we estimate Engel curves, coffee yield and labour input equations incorporating bargaining proxies. We find that income from coffee is increasingly pooled and therefore shared more equally among household members. Yet, we can only detect partial improvements in production efficiency: bargaining still appears to constraint output efficiency and the distribution of household resources continues to follow gendered lines.
Keywords: 330; Market liberalisation; Gender; Bargaining; Intra-household allocation; Sub-Saharan Africa; Uganda